(untitled) (Research, Society and Development, 2020)
Growing demand for safe foods coupled with the intent to reduce food waste, seeing as much of it is lost through contamination by spoilage microorganisms, leads to research on antimicrobial agents such as LAE (Nα-lauroyl-L-arginine ethyl ester monohydrochloride). This compound has great antimicrobial potential against a range of microorganisms and, therefore, its use may be of extreme importance for the food industry in the search for antimicrobial agents with a broad spectrum of action. Thus, the objective of this article is to review the research involving LAE, when studied in vitro, in vivo and in the incorporation in different packaging in order to be released in a controlled manner for food products. In conclusion, despite the fact that it has a strong antimicrobial activity, it is still little known and is not accepted in all countries, including Brazil. With greater insight into this antimicrobial agent, more countries could use it, supporting worldwide in food preservation.